Evaluation of T- Helper (Th-1) Cytokines during the Treatment Responses of chronic Hepatitis C Virus - Al-Khazraji, Khalid A.; AL- Obeidy, Eman Sh. (Journal of the Faculty of Medicine Baghdad, 2009)
Background:It is widely assumed that cellular immune response and cytokine (especially proinflammatory cytokines) production play an important role in the course and treatment effectiveness of chronic hepatitis C infection. Aim of the study: evaluate the level of Th-1 cytokines during treatment of chronic HCV infection and their dynamic changes in response to treatment. Patients and methods: The study was performed on sixty patients with chronic HCV infection, the patients were recruited from medical city gastroenterology and hepatology teaching hospital for the period from February 2007 till February 2008 and 50 healthy control group. Diagnosis was made using third generation ELISA-based screening test, RIBA-based test and PCR-based test. On the other hand, Cytokines (serum level) were determined by ELISA method before, during (6, 12, 24 weeks) and after the treatment. Results: This study showed that after 6 weeks from the initiation of the treatment by pegilated interferon-α in the combination with ribavirin, concentration of serum cytokines IL-1β, TNF- α and INF- γ have significantly changed and at the end of the treatment concentration of all cytokines have decreased and this change was statistically significant for all cytokines.Conclusion: dynamic changes of some cytokines during INF- α and ribavirin treatment may be used as a predictor factor for evaluation of the therapy effectiveness.